INFLUENCE OF EXECUTIVE ANNUAL BONUSES ON RISK TAKING AMONG LISTED COMMERCIAL BANKS IN KENYA - Njogu, Lucy Wanjiru; Gekara, Dr. Mouni; Waititu, Dr. Gichuhi A.; Omido, Dr. Karim (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to determine the influence of executive annual bonuses on risk taking among listed commercial banks in Kenya. Methodology: The study used an Epistemology research philosophy, causal research design was adopted whereby panel data approach was used. The target population for this study were the 11 listed banks on the NSE. Secondary Data for the year 2010 to 2015 was collected from the NSE handbook. Data collected was analyzed using descriptive statistics which included means and standard deviations. Inferential statistics such as Pearson correlation and panel regression was also used. The results were presented in form of tables, figures, charts, graphs and trend lines. Results:Regression analysis results indicated that Executive Annual Bonuses and risk taking were negatively and significantly related. Based on the findings the study recommended that banks should pursue optimum compensation policies, which will ensure minimum cost to the bank. Policy recommendation: The study also recommends that executive annual bonus should be considered incrementally while determining executive compensation perks as it has a decreasing effect on risk among banks listed on NSE.